Entrepreneurship and Enterprise: The Influence of Work Experience on Enterprising Tendency – An Empirical Evidence (Malaysian Management Journal, 1992)
This research explores the influence of different types of work experience on business students’ entrepreneurial tendency in higher education. The research reveals that the majority of the students had not any permanent full-time job experience after their secondary education. Those who had experience of a greater number of permanent full-time jobs were found to be more enterprising than those who had a lesser number. However, the result indicates that there was no association between students’ enterprising tendency and having had permanent full-time job is small and large private professional practices and public sector organisations. On the other hand, the results reveal that those who had permanent full-time job in small business organisations are likely to be more enterprising than those who had not. These findings suggest the importance of certain types of work experience, such as working is small and large business organisations, which should be highlighted in enterprise and entrepreneurship development programmes.